2007
DOI: 10.1093/nar/gkl1134
|View full text |Cite
|
Sign up to set email alerts
|

A new method for accurate assessment of DNA quality after bisulfite treatment

Abstract: The covalent addition of methylgroups to cytosine has become the most intensively researched epigenetic DNA marker. The vast majority of technologies used for DNA methylation analysis rely on a chemical reaction, the so-called ‘bisulfite treatment’, which introduces methylation-dependent sequence changes through selective chemical conversion of non-methylated cytosine to uracil. After treatment, all non-methylated cytosine bases are converted to uracil but all methylated cytosine bases remain cytosine. These m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(65 citation statements)
references
References 9 publications
2
63
0
Order By: Relevance
“…All bisulfite-based methylation analysis methods suffer from a considerable amount of measurement variability introduced by the chemical treatment of genomic DNA. To assess the degree of this inherent variability, we previously dissected the method into its four components and measured the variability for each step in the process (10). The results demonstrated that the greatest source of process-dependent variability is the bisulfite conversion reaction (SD ϭ 10-15%).…”
Section: Resultsmentioning
confidence: 99%
“…All bisulfite-based methylation analysis methods suffer from a considerable amount of measurement variability introduced by the chemical treatment of genomic DNA. To assess the degree of this inherent variability, we previously dissected the method into its four components and measured the variability for each step in the process (10). The results demonstrated that the greatest source of process-dependent variability is the bisulfite conversion reaction (SD ϭ 10-15%).…”
Section: Resultsmentioning
confidence: 99%
“…The overall process variability of bisulfite based PCR methods has been reported to result in standard deviations of the quantitative measurement of 5% to 8%. 30,31 The cut-off of 20% was selected to signify a greater than two standard deviation difference. To further exclude false positive results we limited our selection to genes in which at least two CpG units were found to be differentially methylated.…”
Section: Wwwlandesbiosciencecom Epigeneticsmentioning
confidence: 99%
“…This method, which converts cytosine to uracil has been shown to have some limitations, including incomplete conversion and degradation of DNA during treatment, which can result in problems during PCR. 8,9 In addition, this participant may have been separating alleles on an agarose gel (as described in the original publication) instead of an acrylamide gel, which could also be responsible for sizing errors. Based on these data, bisulfite PCR seems not to be an optimum method for sizing alleles.…”
Section: Stratifying Analytic Performance For Us Participants By Testmentioning
confidence: 99%